Essential Oils and Land Utilization in North-Eastern States - Saha, B.N. (Journal of Soil and Water Conservation, 2022)
The paper deals with the land and water resources in the north eastern states and need for their conservation for economic stability and production system. It has been found that certain plant species are useful for growing on wastelands and area affected by Jhum cultivation. Java citronella has been found to be very useful and beneficial for growing in this region for extraction of essential oil and thereby improving income of the people in this area.